Theories of Modern Art: A Source Book by Artists and Critics - Chipp, Herschel Browning; Selz, Peter 1919-2019; Taylor, Joshua C. 1917-1981 (Berkeley, CA University of California, 1968)
Herschel B. Chipp's Theories of Modern Art: A Source Book By Artists and Critics is a collection of texts from letters, manifestos, notes and interviews. Sources include, as the title says, artists and critics—some expected, like van Gogh, Gauguin, Apollinaire, Mondrian, Greenberg, just to name a few—and some less so: Trotsky and Hitler, in the section on Art and Politics. The book is a wonderful resource and insight into the way artists think and work.
Keywords: 20th Century (1901-2000); Esthetics; Philosophy; Fine art